Summer : Julian Schnabel : paintings 1976-2007 - Moos, David; Sperone, Gian Enzo; Voena, Marco; Schnabel, Julian; Exhibition Rome, Palazzo Venezia 2007-05,03; Exhibition Milan, Rotonda della Besana 2007-06,26; Exhibition International Contemporary Centerof San Sebastián, San Sebastián 2007-07,27 (Milano : Skira, 2008)
- For Julian Schnabel / William Gaddis ##- Notes from Clarkson / Gian Enzo Sperone ##- Paintings and Their Surroundings / Max Hollein ##- Scene by Scene: Ten Paintings by Julian Schnabel from 1976 to Today / David Moos ##- Notes all Julian Schnabel's Untitled (surfer) Paintings / David Moos and Bruce Ferguson ##- The Christ's Last Day Paintings / Julian Schnabel and Louise Neri ##- The Camera Blinks / David Salle ##- Julian Painted a Portrait / Marco Voena ##- Julian Schnabel - Biography and Quotes / Ingrid Pfeiffer.
Published on the occasion of the traveling exhibition, Julian Schnabel, paintings 1976-2000, Rome, Palazzo Venezia, May 3-June 17, 2007; Milan, Rotonda della Besana, June 26-September 30, 2007; Tabacalera, International Contemporary Center of San Sebastián in San Sebastián, Spain, July 27-October 21, 2007; and of the concurrent exhibition, Julian Schnabel: versions of Chuck and other works, Schloss Derneburg, Derneburg, Germany, June-October 2007
boek
Keywords: Schnabel , Julian